A Review of Nutrient Losses to Waters From Soil- and Ground-Based Urban Agriculture—More Nutrient Balances Than Measurements - van de Vlasakker, Paulien C. H.; Tonderski, Karin; Metson, Geneviève S. (Frontiers in Sustainable Food Systems, 2022)
Urban agriculture has a high potential to contribute to local circular economies, for instance by using nitrogen, phosphorus, and potassium in city organic waste streams as fertilizer inputs. However, inefficient use of waste-derived fertilizers could contribute local water quality impairment related to nitrogen and phosphorus losses. Organic waste derived fertilizers are particularly challenging from a nutrient stoichiometry perspective, making over- and under-application of a particular nutrient likely. Where, and under what conditions, urban agriculture acts as a net positive for a circular nutrient economy versus a nutrient water quality risk remains unclear. Here we review empirical peer-reviewed studies (2000-2021) on ground-based urban agriculture with a stated concern for nutrient losses to water. Of the 20 publications reviewed (out of 241 screened), there were four experimental studies of which three measured nutrient leachate losses under different garden management practices. Of the 16 studies done in real world conditions, only four quantified losses to water as leachate; average losses spanned 0.005 to 6.5 kg ha-1 for phosphorus, and 0.05 to 140 kg ha-1 for nitrogen. Thirteen of the 16 non-experimental studies provided data on nutrient inputs and harvested crop outputs, which could be used to calculate garden nutrient balances – an indicator of nutrient use efficiency and risk of losses. Although the value ranges were large, most studied gardens showed nutrient surpluses (inputs > crop harvest) for nitrogen and phosphorus (but not potassium); these surpluses were identified as a risk for losses to water. Contextual factors such as different access to fertilizers and knowledge, along with regulations and environmental factors can help explain the wide range of balance values and nutrient losses observed. Although a large surplus of inputs was often linked to increased leachate losses, it was not always the case in the limited number of studies we identified. Our review suggests that more field studies that measure losses to waters, and document contextual factors, are needed to determine how urban agriculture may contribute to a sustainable circular economy for all three nutrients without nutrient-related water quality impairment.